2013
DOI: 10.5539/jfr.v2n6p48
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Essential Oils From Some African Spices Against Two Strains of Bacillus cereus Isolated From Vegetable Salad

Abstract: Chemical preservatives have been used to preserve our foods against spoilage and pathogenic microorganisms over the years. Consumers now frown at this hence the need to source for preservatives from natural sources. In this investigation fifteen samples of vegetable salad were collected from retail outlets in Lagos, Nigeria dilutions of which were plated on Brilliance Bacillus cereus agar. Isolates were identified based on morphological, biochemical characteristics and reactions to API 20E and API 50 CHB/E tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
3
1
Order By: Relevance
“…The high density of bacterial pathogens isolated from the presents study are similar to those reported by Uzeh et al, (2009) and Eni et al, (2010) where bacterial population as high as 9.9×10 6 was reported. Within the stores, bacterial contaminants contaminate the produce, and multiply when the environmental conditions are favorable (Abadias et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…The high density of bacterial pathogens isolated from the presents study are similar to those reported by Uzeh et al, (2009) and Eni et al, (2010) where bacterial population as high as 9.9×10 6 was reported. Within the stores, bacterial contaminants contaminate the produce, and multiply when the environmental conditions are favorable (Abadias et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…is is contrary to minimum inhibitory concentration of 31.25 mg/mL against Bacillus cereus [53] and that of 1.51 mg/ mL against Enterococcus aerogenes, Staphylococcus aureus, and Proteus mirabilis [54] in the previous studies with A. melegueta.…”
Section: Discussioncontrasting
confidence: 70%
“…Though NDME and DME, respectively, inhibited 60% of the isolates at concentrations ranging between 0.08 and 0.63 mg/mL, DME showed a better antibacterial activity. This is contrary to minimum inhibitory concentration of 31.25 mg/mL against Bacillus cereus [ 53 ] and that of 1.51 mg/mL against Enterococcus aerogenes , Staphylococcus aureus , and Proteus mirabilis [ 54 ] in the previous studies with A. melegueta . The difference in the antibacterial activity of NDME and DME could be attributed to the inhibitory effect of the fatty portion of the plant material.…”
Section: Discussionmentioning
confidence: 62%
“…24,25 In addition, the seed essential oil inhibited the in vitro proliferation of Bacillus cereus, an important causative agent of foodborne illness. 26 An ethanolic seed extract also reduced paw edema in laboratory rats in a process involving inhibition of cyclooxygenase-2 (COX-2) activity, 27 and 6-paradol and 6-shogaol stimulated the expression of proinflammatory genes in an assay for proinflammatory gene expression. 27 These findings are in accordance with the traditional use of A. melegueta against inflammatory conditions.…”
Section: Aframomum Melegueta K Schummentioning
confidence: 99%